Neurocognitive Performance is Not Degraded After Stellate Ganglion Block Treatment for Post-Traumatic Stress Disorder: A Case Series. Issue 5 (1st May 2015) - Mulvaney, Sean W.; Lynch, James H.; de Leeuw, Jason; Schroeder, Matthew; Kane, Shawn
ABSTRACT: Objective: To measure key neurocognitive performance effects following stellate ganglion block (SGB) administered to treat post-traumatic stress disorder (PTSD) symptoms. Methods: Eleven patients diagnosed, screened, and scheduled for SGB to treat their PTSD symptoms were administered a panel of eight cognitive measures before and 1 to 3 weeks after undergoing this procedure. PTSD symptoms were evaluated using the Posttraumatic Stress Disorder Checklist—Military. Results: One to three weeks post-SGB, none of the patients showed any statistically significant decline in neurocognitive performance. Rather, there was a clear trend in improvement, with four out of eight measures reaching statistical significance following SGB. All patients improved in PTSD symptoms with a mean improvement on Posttraumatic Stress Disorder Checklist—Military of 29. Conclusion: In this case series of 11 patients, SGB effectively treated PTSD symptoms and did not impair reaction time, memory, or concentration. Therefore, SGB should be considered as a viable treatment option for personnel with PTSD symptoms who will be placed in demanding conditions such as combat.